Somatostatin Receptor Expression in Lung Neuroendocrine Tumors: An Analysis of DOTATATE PET Scans - Al-Toubah, Taymeyah; Montilla-Soler, Jaime; El-Haddad, Ghassan; Haider, Mintallah; Strosberg, Jonathan (Journal of Nuclear Medicine, 2023)
Somatostatin receptor (SSTR) expression in metastatic lung neuroendocrine tumors (NETs) has not been well characterized using PET imaging. Understanding the degree and uniformity of SSTR expression is important to establish the role of SSTR-targeted treatments in lung NETs. A retrospective institutional review of patients with metastatic lung NETs who underwent DOTATATE PET imaging from March 2017 to February 2023 was performed. In total, 48 patients with metastatic lung NETs who underwent Ga- or Cu-DOTATATE PET imaging were identified. Four had completely negative SSTR expression, and 10 had very weak expression (less than in a normal liver). Among the remaining 34 patients, 21 had uniformly positive DOTATATE PET scans, and 13 had heterogeneous expression. Only 44% had uniformly positive receptor expression, identifying them as candidates for peptide receptor radionuclide therapy. Most metastatic lung NETs lack uniform SSTR expression and are thus suboptimal candidates for SSTR-targeted therapy. SSTR imaging in lung NETs should be evaluated carefully for uniformity of expression.